2005
DOI: 10.2166/wst.2005.0030
|View full text |Cite
|
Sign up to set email alerts
|

Effective pollutant retention capacity of permeable pavements for infiltrated road runoffs determined by laboratory tests

Abstract: The infiltration of urban runoff always implies an entrance of pollutants into the soil and ground water. Due to legal regulations in many communes there is no longer any permission needed for stormwater infiltration, if administrative regulations and the requirements of standards are observed. The results of a research project carried out under the heading "Development of an assessment procedure for permeable pavements" show, that the pollutant retention capacity of permeable pavements varies considerably, de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…A reduction in the concentration of heavy metals such as zinc, copper and lead has also been found in studies undertaken in the field and laboratory (Dierkes et al, 2005;Fach and Geiger, 2005). The current study assessed the retention of dissolved heavy metal contaminants when they are added directly to the basecourse reservoir, excluding the processes of filtration and sorption that occur in the upper layers of the permeable pavement structure shown in Figure 1.…”
Section: Change In Heavy Metal Concentrationsmentioning
confidence: 58%
See 1 more Smart Citation
“…A reduction in the concentration of heavy metals such as zinc, copper and lead has also been found in studies undertaken in the field and laboratory (Dierkes et al, 2005;Fach and Geiger, 2005). The current study assessed the retention of dissolved heavy metal contaminants when they are added directly to the basecourse reservoir, excluding the processes of filtration and sorption that occur in the upper layers of the permeable pavement structure shown in Figure 1.…”
Section: Change In Heavy Metal Concentrationsmentioning
confidence: 58%
“…The type of rock used for the bedding and basecourse aggregate of the permeable pavement was not reported. Fach and Geiger (2005) assessed the sorption of zinc, copper and lead to several permeable pavement construction materials in a laboratory study that included crushed basalt and limestone basecourse materials. Limestone showed a superior ability to absorb these heavy metal contaminants.…”
Section: Introductionmentioning
confidence: 99%
“…Fach and Geiger [88] used four types of permeable concrete blocks to remove significant amounts of such metals ie Cd, Cu, Pb, and Zn from artificial rainfall-runoff events. Myers et al [89] reported 94 to 99% reduction of Zn, Cu, and Pb in water stored in permeable pavement after time duration of 144 h. Other researchers observed 80% removal of Zn [86].…”
Section: Permeable Pavementsmentioning
confidence: 99%
“…However, the studies so far focused on parking areas or roads, and few studies mention the pavement joints of sealed or partially-sealed surfaces as an urban interface, which can act as a source or sink of heavy metals (Dierkes et al, 1999;Dierkes et al, 2004;Dierkes et al, 2005a). Furthermore, the pollution retention capability of pavement joints has mostly been determined in laboratory tests and not in the field (Fach and Geiger, 2005).…”
Section: Introductionmentioning
confidence: 99%